(3GdSfOGJ GdMchejIs - (3HQGjGf chjd (B.s; (3HQGjGf chjd (B.s ((3GdbGgQI (B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B,s, 2006)
(3jJfGhd GdcJGH GdSfOGJ GdMchejI GdOhdjI MjK GfI jYed Ydi JhVjM GdSeGJ GdNGUI HgG h jbOe TQMG hGajG dCShGb GdSfOGJ ai cd ef GdeedcI GdeJMOI h GdhdGjGJ GdeJMOI h GdeGfjG h GdjGHGf , GjVG jJfGhd TQMG dhSGFd GdGbJQGV h GShGb GdCbJQGV WhjdI GdCLd h cPdc SjhdI MQcJi GdHjY h GdTQGA(B.s
(3GdSfOGJ GdMchejI(B.s
All age.
Keywords: (3GdSfOGJs -- (3GdMcheI(B.s